2022
DOI: 10.1007/s11127-022-01002-3
|View full text |Cite
|
Sign up to set email alerts
|

The pox of politics: Troesken’s tradeoff reexamined

Abstract: In The Pox of Liberty , Werner Troesken details the tradeoff between liberal institutions and communicable disease. According to Troesken, individual freedom presents a danger to the public health in the face of infectious disease, while constitutional constraints restrict the government’s ability to implement effective policy. Contra Troesken, I argue that decision-makers, amidst a crisis of contagion, neglect intertemporal tradeoffs, thereby discounting long run costs while favoring sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…Addressing the problems presented by the COVID-19 pandemic, researchers in liberal political economy have challenged the supposed trade-off between protection against infectious disease and economic freedom (Furton, 2023 ; Geloso et al, 2021 ; Geloso & Murtazashvili, 2021 ; Koyama, 2023 ), shown that political incentives encourage officials to adopt stricter measures than is economically efficient (Allen, 2022 ; Boettke & Powell, 2021 ; Hebert & Curry, 2022 ; Leeson & Thompson, 2023 ; Murtazashvili and Zhou this volume ; cf. Garzarelli et al, 2022 ), including measures that persist after the danger has passed (Goodman et al, 2021 ), proposed that spontaneous endogenous citizen responses to novel infections are more effective than typically predicted (Allen et al, 2022 ; Leeson & Rouanet, 2021 ), and highlighted how decisions in the private sector can internalise many of the relevant externalities associated with the infection (Albrecht & Rajagopalan, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the problems presented by the COVID-19 pandemic, researchers in liberal political economy have challenged the supposed trade-off between protection against infectious disease and economic freedom (Furton, 2023 ; Geloso et al, 2021 ; Geloso & Murtazashvili, 2021 ; Koyama, 2023 ), shown that political incentives encourage officials to adopt stricter measures than is economically efficient (Allen, 2022 ; Boettke & Powell, 2021 ; Hebert & Curry, 2022 ; Leeson & Thompson, 2023 ; Murtazashvili and Zhou this volume ; cf. Garzarelli et al, 2022 ), including measures that persist after the danger has passed (Goodman et al, 2021 ), proposed that spontaneous endogenous citizen responses to novel infections are more effective than typically predicted (Allen et al, 2022 ; Leeson & Rouanet, 2021 ), and highlighted how decisions in the private sector can internalise many of the relevant externalities associated with the infection (Albrecht & Rajagopalan, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Koyama rightly recognizes such progress as a genuine challenge to liberal institutions and their apologists—one that must be taken up by serious social scientists going forward. Furton ( 2022 ) takes up the challenge, contending that the alleged tradeoff between public health and individual liberty likely is overstated. He argues that political involvement in public health reform tends to occur during health crises , wherein policies are passed under conditions of extreme urgency and uncertainty.…”
mentioning
confidence: 99%